The greatest show of all - Eagland, Jane (Edinburgh: Barrington Stoke, 2016)
Kitty's father won't let her follow her dreams and so, when Huxley's Circus comes to town, she disguises herself as a stable-lad and is taken on under the name of Kit. In her new role Kitty works with dark-eyed, curly-haired Jack and falls head over heels. But Jack is in love with Sara the tightrope-walker. But Sara has a secret of her own
Keywords: Young adult fiction